A Nearly Lethal Screw: An Unusual Cause of Recurrent Bradycardia and Asystole Episodes after Fixation of the Cervical Spine. (12th October 2017) - Frenkel, Amit; Binyamin, Yair; Brotfain, Evgeni; Koyfman, Leonid; Roy-Shapira, Aviel; Shelef, Ilan; Klein, Moti
Abstract : We present a case of a 51-year-old man who was injured in a bicycle accident. His main injury was an unstable fracture of the cervical and thoracic vertebral column. Several hours after his arrival to the hospital the patient underwent open reduction and internal fixation (ORIF) of the cervical and thoracic spine. The patient was hospitalized in our critical care unit for 99 days. During this time patient had several episodes of severe bradycardia and asystole; some were short with spontaneous return to sinus and some required pharmacological treatment and even Cardiopulmonary Resuscitation (CPR). Initially, these episodes were attributed to the high cervical spine injury, but, later on, CT scan suggested that a fixation screw abutted on the esophagus and activated the vagus nerve by direct pressure. After repositioning of the cervical fixation, the bradycardia and asystole episodes were no longer observed and the patient was released to a rehabilitation ward. This case is presented in order to alert practitioners to the possibility that, after operative fixation of cervical spine injuries, recurrent episodes of bradyarrhythmia can be caused by incorrect placement of the fixation screws and might be confused with the natural history of the high cervical cord injury.